Magnesium depletion scores as a risk factor for prevalence and mortality rates of urinary incontinence: a national survey analysis - Xia, Ping; Shi, Xiaolong; Yang, Yunling; Zhang, Yanru; Hu, Xuyang; Lin, Rong; Weng, Xiaoying; Shen, Fenfang; Chen, Xiaobao; Lin, Liang (Frontiers in Nutrition, 2025)
BackgroundMagnesium regulates vascular smooth muscle contraction, with implications for cardiovascular diseases. However, the population-level relevance of magnesium homeostasis to urinary incontinence (UI) subtypes and associated mortality remains unexamined.MethodsThe National Health and Nutrition Examination Survey (NHANES) were utilized to investigate the association between magnesium depletion score (MDS) and urinary incontinence (UI) from 2005 to 2018. Weighted multivariate regression analyses and multivariate Cox regression analyses were used to analysis. Additionally, subgroup analyses and multiple imputations (MI) were carried out as sensitivity analyses to ensure the strength and reliability of the findings.ResultsA total of 16,197 individuals were included in the study, with 6,881 of them experiencing urinary incontinence (UI). Among those with UI, 767 cases of all-cause mortality were documented. The prevalence rates were 42.83% for stress urinary incontinence (SUI), 27.85% for urgency urinary incontinence (UUI), and 16.82% for mixed urinary incontinence (MUI). Results from weighted logistic regression analysis demonstrated a positive relationship between MDS and SUI (OR 1.09, 95% CI: 1.01–1.17), UUI (OR 1.14, 95% CI: 1.06–1.22), and MUI (OR 1.22, 95% CI: 1.11–1.35). Additionally, higher MDS values were associated with increased severity of urinary incontinence. These findings were further supported by various sensitivity analyses. Furthermore, survey-weighted Cox proportional hazards regression indicated a positive association between MDS and all-cause mortality regardless of (OR 1.27, 95% CI: 1.13–1.41), suggesting that higher MDS independently predicts worse prognosis.ConclusionMDS is an important risk factor for the prevalence and mortality rates of UI. Monitoring magnesium status may inform UI prevention strategies. Interpretation should consider limitations including observational design and lack of serum magnesium levels.